2004
DOI: 10.1038/sj.bjc.6601832
|View full text |Cite
|
Sign up to set email alerts
|

Expression of EBAG9/RCAS1 is associated with advanced disease in human epithelial ovarian cancer

Abstract: Oestrogen receptor-binding fragment associated gene 9, EBAG9, is an oestrogen-responsive gene that was identified in MCF-7 human breast carcinoma cell line. It is identical to RCAS 1, a cancer cell surface antigen possibly involved in immune escape. In the present study, we examined the expression of EBAG9/RCAS1 in human epithelial ovarian cancer using immunohistochemistry, immunoblotting and reverse transcription -polymerase chain reaction (RT -PCR). A total of 90 epithelial ovarian cancer cases were examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 31 publications
2
34
0
1
Order By: Relevance
“…In vivo transcriptional changes induced by p53 mutants have also been reported previously by us and others (16). Of the genes identified in our microarray, MCL1 EBAG9, ANGPT1, ITGA6, NFB2, and E2F-5 expression has been reported as up-regulated in various cancer types (33)(34)(35)(36)(37)(38). Because information is not available in the literature, it remains to be seen whether these genes are up-regulated in the natural context of the p53 mutation, i.e., in human cancers carrying a p53 mutation.…”
Section: Discussionsupporting
confidence: 49%
“…In vivo transcriptional changes induced by p53 mutants have also been reported previously by us and others (16). Of the genes identified in our microarray, MCL1 EBAG9, ANGPT1, ITGA6, NFB2, and E2F-5 expression has been reported as up-regulated in various cancer types (33)(34)(35)(36)(37)(38). Because information is not available in the literature, it remains to be seen whether these genes are up-regulated in the natural context of the p53 mutation, i.e., in human cancers carrying a p53 mutation.…”
Section: Discussionsupporting
confidence: 49%
“…As we showed that there are several types of cancer that intensely express EBAG9 and the expression levels of EBAG9 may relate to advanced tumor grades (3)(4)(5)(6), it is likely that the tumorpromoting effect of EBAG9 is a general event in malignancies regardless of their estrogen dependency. We also observed the lack of association between sex and EBAG9 expression in human RCC in our clinicopathologic study (Supplementary Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…EBAG9 is an estrogen-inducible, ubiquitously expressed protein with close homologues in human and murine rodents that exhibits a Golgi-predominant localization in nonneuronal cells Engelsberg et al, 2003). This raised the question of what function EBAG9 under physiological conditions has and whether this function relates to its proposed tumor association (Ikeda et al, 2000;Kubokawa et al, 2001;Suzuki et al, 2001;Tsuneizumi et al, 2001;Leelawat et al, 2003;Akahira et al, 2004). Using full-length EBAG9 as the bait to screen a human brain cDNA library, we identified Snapin as an interaction partner of EBAG9 and verified the relevance of this interaction in exocytosis assays.…”
Section: Introductionmentioning
confidence: 99%